Effects of Mimosa pudica L. leaves extract on anxiety, depression and memory - Patro, Ganesh (Avicenna J Phytomed, 2016)
OBJECTIVE: The present study was carried out to investigate the neuropharmacological activities of ethyl acetate extract of Mimosa pudica (EAMP) leaves on anxiety, depression and memory in a mouse model. MATERIALS AND METHODS: Anti-anxiety potential of EAMP was evaluated by elevated plus maze (EPM), light-dark box (LDB) and social interaction (SI) tests in mice.Anti-depressant potential of EAMP was evaluated by forced swimming (FST), tail suspension (TST), and open field tests (OFT). The behavioral findings were further corroborated with estimation of neurotransmitters and their metabolites from mouse brain homogenate. Effect on learning and memory was evaluated by EPM, passive avoidance (PA) tests. Further, it was confirmed with assessment of acetylcholinesterase and caspase-3 activity in brain homogenate. RESULTS: EAMP showed significant anti-anxiety activity by increasing the time spent in open arm of EPM, light box of LDB. Social interaction time was increased significantly (p<0.01) as compared to vehicle control. There was also significant reduction of immobility time in both FST and TST without any changes in locomotor activity in the OFT. Monoamine neurotransmitters (dopamine and norepinephrine) concentrations were increased significantly (p<0.01) after 4 weeks of treatment as compared to stress control and substantiated the anti-depressant activity. Step down latency was increased (p<0.01) in PA test and transfer latency was decreased (p<0.01) in EPM test of EAMP-treated mice. Acetylcholinesterase and caspase-3 activity was significantly (p<0.05) changed in mice treated with EAMP (200 and 400 mg/kg). CONCLUSION: The results revealed that EAMP has anti-anxiety, anti-depressant and memory enhancing activities that are mediated through multiple mechanisms.